To be like a “scholar”: a study on the construction of authorial identity of Chinese EFL learners in academic writing: an intertextuality perspective - Zhang, Lei; Wang, Jing (Frontiers in Psychology, 2024)
Academic writing not only conveys academic content but also represents the authorial identity, serving as a means of presenting one’s identity. Writers utilize various linguistic resources to present different possibilities of self, such as intertextuality, thereby constructing their authorial identity. This study examines the Chinese EFL learners’ construction of authorial identity in academic writing from an intertextuality perspective.This study adopts a mixed method, utilizing interviews and written texts as data sources. Results were found that novice writers primarily construct their identities through the practices of direct intertextuality during the initial stages of identity construction. As novice writers gain more experience through extensive reading and writing practices, as well as academic writing courses, their intertextuality practices undergo a transformation. They begin to shift from direct intertextuality to indirect intertextuality, aiming to express their own conceptions, attempting to be like a “scholar” through indirect intertextuality.The study highlights the importance of intertextuality in the construction of academic writing identity for EFL learners. By understanding the interplay between intertextuality and authorial identity, educators can better assist EFL learners in achieving success in their academic writing endeavors.